O lugar da paisagem nos olhares do pensamento: de Alagoas a Maceió, narrativas e visualidades - Gusmão, Ana Caroline Sarmento Cavalcanti de (2010)
The state of Alagoas is now recognized for its natural beauty, underpinned by images of beaches, shaped particularly by the ambience of the seaside of Maceió. The identity of the landscape is recognized by its bluish green waters amidst a radiant solar atmosphere. In this contemporary context, there is the issue to be investigated in the course of this dissertation: is this landscape identity in accordance with spontaneity? Or we can identify a historical background in which this visual identity can be understood as a cultural process? And, if so, how are guided textual and pictorial representations in the construction of this image of the local landscape? The survey was developed from the identification and analysis of sources made between the eighteenth century - when the county of Alagoas emerges - and the twentieth century - during which the city of Maceió consolidates as the new capital. With this time frame, we tried to cover the initial representations about the land comprised in the territory of Alagoas, reaching the first pictorial images of their capital. Session 1 discusses the concept of landscape, installing from there, the essential issues to be worked on in later sessions. The second session is devoted to the formalization of the initial aspects of the construction of identity of Alagoas, where we will highlight some literary narratives. It was found that writing about the area is summed up in two ambiances-specifically: the forests and the cane fields. Session 3 investigates narratives of geographical character, related in particular to the context of consolidation of the city of Maceio as the new capital. Session 4 dwells on the analysis of visual representations of the place, especially the lithographs by Ricardo Manuel Couto, and in particular, the work of the painter José Paulino.